PEMERIKSAAN STATUS GIZI ANAK USIA PRA- SEKOLAH DI TK AISYIYAH KEMANTREN TULANGAN SIDOARJO - Purwanti, Yanik; Yuliartanti , Windy; Wisaksono , Arief (Journal of Social Comunity Services, 2024)
East Java is still facing nutritional and child health problems. It is important for society, especially young mothers, to realize how important the nutritional needs of children are. This is because a child's nutritional condition directly affects their physical and mental growth and development. From an early age, it is important to monitor the child's development regularly. In an effort to obtain high-quality human resources, this is done. The growth of the golden period, or golden age, occurs during the first five years of a child's life. Monitoring development from an early stage is crucial to obtaining the right information to provide the right stimulation and nutrition. In the service of this community, we use the method of measuring the nutritional status of young people at Aisyiyah Kempantren Sidoarjo. We used anthropometric standards of weight based on age (Body fat/age) and height based upon age (Height/age), as defined by the WHO. The results showed that 91.89% (68 people out of 74 young people) had good nutritional status, and 8.11% of 6) had better nutritional/obesity status. Teachers and parents are advised to pay more attention to student nutrition so that they can get good nutrition for student health